Managing Public Debt and Its Financial Stability Implications - Das, Udaibir (IMF Working Papers; Working Paper ;, 2010)
This paper explores the relationship between the level and management of public debt and financial stability, and explains the channels through which the two are interlinked. It suggests that the broader implications of a debt management strategy and its implementation should be carefully analyzed by debt managers and policy makers in terms of their impact on the government's balance sheet, macroeconomic developments, and the financial system.